2022
DOI: 10.1186/s12911-022-01809-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a system to assist in clinical decision-making in primary healthcare in Catalonia: prescription Self Audit

Abstract: Background In 2008, in the context of a complete computerisation of medical records, the Institut Català de la Salut (ICS, Catalan Health Institute) implemented a system in its electronic clinical workstation (ECW) to assist decision-making at the prescription level. This system is known as Self Audit, and it supports physicians in reviewing the medication of their patients. Self Audit provides lists of patients presenting medication-related problems (MRPs) that have potential for improvement, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
3
0
1
Order By: Relevance
“…In a scoping review, the clinical validation of several CDSSs for drug-related problems revealed a sensitivity of 28%–85% and a specificity of 42–75% [ 36 ], though these were not studies of CDSS for TW management. A general acceptance rate above 60% is suggested for action-oriented interventions [ 37 ]; our TW algorithm compliance rate was 77.7%, which compares favourably with this standard and with the acceptance rates reported for primary care TW CDSSs (30–82%) [ 26 , 28 , 29 ]. The acceptance rate differed between the alerts and was highest within patients with a kidney function below 30 ml/min/1.73m2.…”
Section: Discussionsupporting
confidence: 69%
“…In a scoping review, the clinical validation of several CDSSs for drug-related problems revealed a sensitivity of 28%–85% and a specificity of 42–75% [ 36 ], though these were not studies of CDSS for TW management. A general acceptance rate above 60% is suggested for action-oriented interventions [ 37 ]; our TW algorithm compliance rate was 77.7%, which compares favourably with this standard and with the acceptance rates reported for primary care TW CDSSs (30–82%) [ 26 , 28 , 29 ]. The acceptance rate differed between the alerts and was highest within patients with a kidney function below 30 ml/min/1.73m2.…”
Section: Discussionsupporting
confidence: 69%
“…Regarding the therapeutic duplications, excluding the prevalence of vitamin D or analogs associated with calcium, the rest was observed to be due to patients who are undergoing drug dose adjustments or changes. Both PREFASEG and Self-Audit detect therapeutic duplication, which helps explain the low percentage of duplications detected in this medication review ( Pons-Mesquida et al, 2021 ; 2022 ). In a recent study done in a pediatric health system, where they designed clinical decision support to reduce therapeutic duplication with acetaminophen and ibuprofen, they saw a therapeutic duplication reduction, but it was associated with high rates of user frustration and alert fatigue ( E Dawson et al, 2023 ).…”
Section: Discussionmentioning
confidence: 82%
“…Government of Catalonia, 2022 ). The main sources of information used by the clinical pharmacologist to conduct the review and give recommendations comprised the information contained in the technical data sheets, the support tools Self-Audit and PREFASEG (PREscripción FArmacéutica SEGura) ( Pons-Mesquida et al, 2021 ; 2022 ), and the list of potentially inappropriate drugs proposed by the Catalan Health Service ( Department of Health. Government of Catalonia, 2014 ; Catalan Health Service.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…En el ámbito de AP, la Estación Clínica de Atención Primaria (ECAP) es el programa de historia clínica electrónica (HCE) utilizado por los profesionales sanitarios del Institut Català de la Salut (ICS). Integrado en dicha HCE, a nivel de prescripción, encontramos dos sistemas de apoyo a la toma de decisiones clínicas, el PREFASEG 10 y el Self Audit 11 , cuyo objetivo es fomentar la seguridad clínica en el uso de medicamentos.…”
Section: Introductionunclassified